Multiplicity dependence of two-particle azimuthal correlations in pp collisions at the LHC - Abelev, B.; Adam, J.; Adamova, D.; Adare, A. M.; Aggarwal, M. M.; Rinella, G. Aglieri; Agnello, M.; Agocs, A. G.; Agostinelli, A.; Ahammed, Z.; Masoodi, A. Ahmad; Ahmad, N.; et al. (SPRINGER, 2013)
We present the measurements of particle pair yields per trigger particle obtained from di-hadron azimuthal correlations in pp collisions at root s = 0.9, 2.76, and 7TeV recorded with the ALICE detector. The yields are studied as a function of the charged particle multiplicity. Taken together with the single particle yields the pair yields provide information about parton fragmentation at low transverse momenta, as well as on the contribution of multiple parton interactions to particle production. Data are compared to calculations using the PYTHIA6, PYTHIA8, and PHOJET event generators.
Keywords: Hadron-Hadron Scattering; DISTRIBUTIONS; Physics